The landscape of chromothripsis across adult cancer types - Natalia Voronina; John K. L. Wong; Daniel Hübschmann; Mario Hlevnjak; Sebastian Uhrig; Christoph E. Heilig; Peter Horak; Simon Kreutzfeldt; Andreas Mock; Albrecht Stenzinger; Barbara Hutter; Martina Fröhlich; et al. (Nature Communications, 2020)
The shattering of chromosomes is a dramatic early event in tumourigenesis and is termed chromothripsis. Here, the authors examine chromothripsis across 28 tumour types and show that 49% of cancers exhibit features of chromothripsis.